Chemometric Analysis of Serum Magnesium Calculations Using Mg-Xylidyl Blue-I Method Based on Molar Absorptivity - Ally Kafesa; Nadira Nur Hajah Lutfi; Cep Wahyu (Universitas Nahdlatul Ulama Surabaya, 2021)
The concentration of magnesium is determined based on the absorbance of the Mg-Xylydil Blue-I complex solution use spectrophotometer. Based on the Lambert-Beer rule, the calculation of sample concentration is based on the formula A = Ԑ. b. C. Generally, the thickness of the cuvette (b) and the molar absorptivity (Ԑ) factor will be ignored because it is considered to have a fixed value, therefore the sample concentration is measured based on the ratio of the absorbance of the sample against the standard solution. However, the standard solution contains pure magnesium and has a different matrix than the sample matrix, so this condition can give analytical errors and lead to misinterpretation of the results. The purpose of this study was to determine the accuracy and the precision of serum magnesium calculation by the principle of the Mg- Xylydil Blue-I complex reaction based on molar absorptivity compared to the general method. This research uses comparative study design methods. The serum sample used was the patient's serum specimen who has a normal magnesium level. The results showed that the significance value of the paired t-test statistical was 0.000 (p < 0.05). The accuracy value (d%) of the calculation formula uses Ɛ is 0.00 and the precision value (CV%) is 0.53. While the accuracy value (d%) of the calculation formula without Ɛ is 0.00 and the precision value (CV%) is 0.38. Calculations based on molar absorptivity (Ɛ) can measure more significant serum magnesium than those calculated based on standard magnesium solutions.